Geographical, temporal and taxonomic biases in insect GBIF data on biodiversity and extinction. (23rd February 2021) - Rocha‐Ortega, Maya; Rodriguez, Pilar; Córdoba‐Aguilar, Alex
Abstract : Inventories are incomplete worldwide, except for some areas in Europe. Although the description of new insect species and IUCN‐listed species has increased in the last 40 years, this is biased towards lepidopterans, odonates and coleopterans. Pristine areas worldwide have few insect records. Abstract : 1. Analysis of geographic patterns of extinction must be accompanied by knowledge of biodiversity patterns. Such analysis is not yet available in insects given three shortfalls. First, knowledge of insect species' distribution is poor. Second, insect inventories have taxonomic, geographical, temporal and habitat biases. Third, the accelerated loss of insect species likely surpasses the rate at which the authors are discovering new species. 2. The authors have examined the state of the art of knowledge of the geographical distribution of insect extinction risk and diversity, as well as their relation with human footprint. 3. Insect records are highly scattered. Geographically, inventories are incomplete worldwide, except for some areas in Europe. Although the description of new insect species has increased in the last 40 years, this is biased towards lepidopterans and coleopterans. Comparably, IUCN‐listed species has also increased in the last 40 years, yet with biases towards odonates and lepidopterans. Likewise, aquatic species have been more intensively sampled and considered by the IUCN than terrestrial species. Of high priority are some pristine areas but with few insect records, whereas the east coast of the United States, Europe and Japan raise concerns given that the human footprint exceeded the species richness of insects registered.